Economic process design for separation of CO2 from the off-gas in ironmaking and steelmaking plants. (August 2015) - Kim, Hansol; Lee, Jaewook; Lee, Soobin; Lee, In-Beum; Park, Joo-hyoung; Han, Jeehoon
Abstract: We develop an economic process design for separation of CO2 from the off-gas in ISMPs (iron and steel making plants). Based on the characteristics of the off-gas from which CO2 must be separated, we design two process configurations: PSA (pressure-swing adsorption) and MEA (monoethanolamine)-based chemical absorption. We also develop a simulation model of each process, and perform an economic evaluation of the configurations. Our technical performance analyses show that the CO2 recovery and purity are >90% in the both processes and that highly-concentrated combustible gas (CO and H2 ) can be obtained as a byproduct. Our economic performance analyses show that the designed processes lead to cost-effective and competitive options (62/t CO2 separated), compared to the CO2 separation processes used in power plants. Using the combustible gas as a fuel for the boiler of power cycle greatly reduces the cost of CO2 separation in ISMPs. Highlights: We develop an economic process design for CO2 separation in iron and steel plants. We design two processes: pressure-swing adsorption and chemical absorption. Techno-economic performance analyses of the proposed design are presented.